Sexually transmitted infections in women deprived of liberty in Roraima, Brazil - Maria Soledade Garcia Benedetti; Audrey Stella Akemi Nogami; Beatriz Belo da Costa; Herbert Iago Feitosa da Fonsêca; Igor dos Santos Costa; Itallo de Souza Almeida; Luana de Miranda; Matheus Mychael Mazzaro Conchy; Renan da Silva Bentes; Suzani Naomi Higa; Tháles de Souza Israel; Allex Jardim da Fonseca (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To evaluate the prevalence of HIV, syphilis and hepatitis B infection among women deprived of liberty in the state of Roraima, Brazil, and its correlation with perceptions, knowledge and behavioral factors. METHOD This is a cross-sectional study, with simple systematic sampling, conducted at the Public Female Prison in Boa Vista, State of Roraima, in 2017. A total of 168 inmates (93.8% of the population) were evaluated by in-person interviews and rapid tests. RESULTS The prevalence of sexually transmitted infections (STI) was 20.2%, being 4.7% HIV, 15.5% syphilis, and 0.0% hepatitis B. Multivariate analysis confirmed as risk factors for acquiring an STI: being over 30 years of age [adjusted odds ratio (OR): 2.57; 95%CI 1.03-6.40); low schooling (adjusted OR: 2.77; 95%CI 1.08-5.05); little knowledge about condom use (adjusted OR: 2.37; 95%CI 1.01-7.31); and believing that there is no risk of contracting syphilis (adjusted OR: 2.36; 95%CI 1.08-6.50). CONCLUSION The population deprived of liberty is a group of highly vulnerable to STI. The high prevalence of these infections can be explained by knowledge deficits on the subject, distorted perceptions and conditions peculiar to imprisonment, which result in risky behavior. We emphasize the need to implement educational programs for preventing, diagnosing and treating STI for this population.